A Novel Evaluation Framework for Medical LLMs: Combining Fuzzy Logic and MCDM for Medical Relation and Clinical Concept Extraction - Dianes A/P David Emmanuel, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
A Novel Evaluation Framework for Medical LLMs: Combining Fuzzy Logic and MCDM for Medical Relation and Clinical Concept Extraction by Dianes A/P David Emmanuel, Salem Abdullah Salem Garfan